Spatial experiences of adults with autism spectrum disorder within office environments - Agustin, Rosalie Y.; Gallardo, Mildred M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The purpose of this study was to provide a broader understanding of the spatial experiences, needs, difficulties, and behavioral characteristics of Persons with Autism Spectrum Disorder (ASD) within office environments. The study was conducted among three (3) adults aged 21 and above, who were formally diagnosed with ASD, are employed in an office environment, and are engaged in only clerical, office assistance, or other office-based work activities. A qualitative research methodology using grounded theory was used to explore spatial factors that influence an individual with Autism's experiences with an office. Personal, in-depth interviews were conducted among the respondents, using instrumentation tools such as an interview guide, a voice recording application on a smartphone, and supplementary field notes gathered using pen and paper. The results of the interviews were transcribed and reviewed using open coding, identifying relevant concepts that include the office layout, permanence of workspace, lighting, colors, temperature, air quality, noise, visual elements, cleanliness and organization of the space, and navigation or wayfinding. Selective coding was then used to group similar codes into four encompassing categories, namely freedom from distractions, sensitivity, predictability, and access to permanent workspaces. Several factors emerged, including sensitivity to environmental stimuli such as auditory distractions, certain colors, and the cleanliness and organization of the space. The results also suggest that Persons with Autism prefer workplaces that are free of distractions, are predictable, have neutral colors and cool lighting, and have access to permanent workspaces.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Autistic people -- Employment -- Philippines; Autistic people -- Attitudes -- Philippines; Spatial behavior -- Philippines; Office layout -- Philippines; Interior decoration -- Philippines